1995
DOI: 10.1128/iai.63.12.4675-4681.1995
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha activity in genital tract secretions of guinea pigs infected with chlamydiae

Abstract: Previous studies using the guinea pig model of chlamydial genital infection demonstrated that primary infection is associated with a marked acute inflammatory response early on, while chronic inflammation appears later, at a time when the level of infection is reduced. Challenge infections result primarily in a chronic inflammatory response. The stimuli that initiate inflammation and lead to tissue damage have not been defined. We investigated the possibility that tumor necrosis factors (TNFs) play a role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…It can induce a significant influx of neutrophils and has a strong activating effect on these cells, in addition to other leukocytes and endothelial cells. We have documented high levels of TNF-␣ in the genital tract secretions of guinea pigs during primary chlamydial infection at a time of marked neutrophil influx (4).…”
Section: Discussionmentioning
confidence: 95%
“…It can induce a significant influx of neutrophils and has a strong activating effect on these cells, in addition to other leukocytes and endothelial cells. We have documented high levels of TNF-␣ in the genital tract secretions of guinea pigs during primary chlamydial infection at a time of marked neutrophil influx (4).…”
Section: Discussionmentioning
confidence: 95%
“…Studies on chlamydial infection in animal models indicate that TNF-␣ levels reflect the intensity of current infection (14) and may cause tissue damage which leads to scarring (34). The likely additional role of TNF-␣ in the fibrogenic process of scar formation (25,33) has not yet been investigated in experimental models of chlamydial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TNF-␣ may protect against active chlamydial infection, as it has an antichlamydial effect both in vitro (29,30) and in vivo against the C. trachomatis mouse pneumonitis agent in the lung (35). Secretion of TNF-␣ occurs at the genital site of C. psittaci infection in guinea pigs (14), although its relevance to protection is unknown.…”
mentioning
confidence: 99%
“…TNF-␣ measurement. Because previous data have suggested that PMNs are a significant source of tumor necrosis factor alpha (TNF-␣) (5,38) and since TNF-␣ has frequently been documented as an initiatory cytokine released upon chlamydial invasion of the host (12), the presence of this cytokine in the sera of both depleted and nondepleted mice was determined to establish whether PMNs were the source of TNF-␣ in our infection model. To determine the presence of TNF-␣ in response to chlamydial infection, serum samples were collected from mice at different days p.i.…”
Section: Methodsmentioning
confidence: 99%